Simulasi Sensor Fotodioda Pada Sistem Lampu Otomatis Berbasis Arduino - Putri Nazwa Meylani; Desmira Desmira; Nurma Lestari; Muhammad Rivaldan; Reva Lina Putri Septiani; Elan Maulana (Teknik: Jurnal Ilmu Teknik dan Informatika, 2026)
This study discusses the design and simulation of an automatic lighting system based on a photodiode sensor using an Arduino Uno microcontroller as the main controller. The system is designed to detect changes in ambient light intensity and automatically control the lamp without human intervention. The photodiode sensor is used as a light detector that converts light energy into an analog electrical signal, which is then processed by the Arduino to determine bright or dark conditions. The output from the Arduino subsequently controls a relay module that functions as an electronic switch to connect or disconnect the current to the light bulb. The research method employed is an experimental approach, which includes system planning, hardware design, software programming, simulation using Proteus, and system performance testing. The simulation results indicate that the system operates as expected, where the lamp automatically turns on when the light intensity decreases and turns off when the ambient brightness increases. This system is expected to improve electrical energy efficiency and provide ease of operation for lighting control, particularly in public facilitiesand workplace environments.